Perceptions of Marriage and Human Relationships in Jane Austen’s Novel Emma - Kica, Eljvira (European Scientific Journal, ESJ, 2017)
Emma is a novel written by Jane Austen, which is based on real- life situations of the eighteenth century England. Austen depicts her novels to show clearly the customs and traditions that people had to use in order to get married; her dissatisfaction towards all these conditions; male dominance and also the consideration of women as weak human beings with limited rights. Based on all these issues, Austen chooses different kinds of marriages, mainly based on economical interest. Most of the people in her novels see the marriage as an obligation which had to be fulfilled; most of the girls got involved into a marriage market where parents decided what was good or bad for them. This paper describes the conditions of unmarried and married women Emma; the ways how the unmarried women chose the partners; the ways how Austen compared the conditions of women with the real life situations of the eighteenth century Britain; how she used irony to show her dissatisfaction towards the traditions of that time, and also the real message she conveys to the world.